The incidence, risk factors, and prognosis of acute kidney injury in patients after cardiac surgery - Wang, Xian-dong; Bao, Rui; Lan, Yang; Zhao, Zhen-zhen; Yang, Xin-yue; Wang, Yun-yun; Quan, Zhi-yong; Wang, Jia-feng; Bian, Jin-jun (Frontiers in Cardiovascular Medicine, 2024)
Acute kidney injury (AKI) represents a significant complication following cardiac surgery, associated with increased morbidity and mortality rates. Despite its clinical importance, there is a lack of universally applicable and reliable methods for the early identification and diagnosis of AKI. This study aimed to examine the incidence of AKI after cardiac surgery, identify associated risk factors, and evaluate the prognosis of patients with AKI.This retrospective study included adult patients who underwent cardiac surgery at Changhai Hospital between January 7, 2021, and December 31, 2021. AKI was defined according to the Kidney Disease: Improving Global Outcomes (KDIGO) criteria.Perioperative data were retrospectively obtained from electronic health records. Logistic regression analyses were used to identify independent risk factors for AKI. The 30-day survival was assessed using the Kaplan-Meier method, and differences between survival curves for different AKI severity levels were compared using the log-rank test.Postoperative AKI occurred in 257 patients (29.6%), categorized as stage 1 (179 patients, 20.6%), stage 2 (39 patients, 4.5%), and stage 3 (39 patients, 4.5%). The key independent risk factors for AKI included increased mean platelet volume (MPV) and the volume of intraoperative cryoprecipitate transfusions. The 30-day mortality rate was 3.2%. Kaplan-Meier analysis showed a lower survival rate in the AKI group (89.1%) compared to the non-AKI group (100%, P < 0.001).